OpenCV 4 for Secret Agents : Use OpenCV 4 in secret projects to classify cats, reveal the unseen, and react to rogue drivers, 2nd Edition /: Use OpenCV 4 in secret projects to classify cats, reveal the unseen, and react to rogue drivers, 2nd Edition. (2019) - Howse, Joseph
No abstract available